Adolescents' experience of a rapid HIV self‐testing device in youth‐friendly clinic settings in Cape Town South Africa: a cross‐sectional community based usability study. Issue 1 (23rd December 2016) - Smith, Philip; Wallace, Melissa; Bekker, Linda‐Gail
Abstract : Introduction : Since HIV testing in South African adolescents and young adults is sub‐optimal, the objective of the current study was to investigate the feasibility and acceptability of an HIV rapid self‐testing device in adolescents and young people at the Desmond Tutu HIV Foundation Youth Centre and Mobile Clinic. Methods : Self‐presenting adolescents and young adults were invited to participate in a study investigating the fidelity, usability and acceptability of the AtomoRapid HIV Rapid self‐testing device. Trained healthcare workers trained participants to use the device before the participant conducted the HIV self‐test with device usage instructions. The healthcare worker then conducted a questionnaire‐based survey to assess outcomes. Results : Of the 224 enrolled participants between 16 and 24 years of age, 155 (69, 2%) were female. Overall, fidelity was high; 216 (96, 4%) participants correctly completed the test and correctly read and interpreted the HIV test result. There were eight (3, 6%) user errors overall; six participants failed to prick their finger even though the lancet fired correctly. There were two user errors where participants failed to use the capillary tube correctly. Participants rated acceptability and usability highly, with debut testers giving significantly higher ratings for both. Younger participants gave significantly higher ratings of acceptability. Conclusions : Adolescents and young adults found HIV self‐testing highly acceptable with the AtomoRapid and they used the device accurately. Further research should investigate how, where and when to deploy HIV self‐testing as a means to accompany existing strategies in reaching the UNAIDS goal to test 90% of all individuals worldwide.